Comparison of the c‐MET gene amplification between primary tumor and metastatic lymph nodes in non‐small cell lung cancer. Issue 5 (7th June 2017) - Xu, Chun‐wei; Wang, Wen‐xian; Wu, Mei‐juan; Zhu, You‐cai; Zhuang, Wu; Lin, Gen; Du, Kai‐qi; Huang, Yun‐jian; Chen, Yan‐ping; Chen, Gang; Fang, Mei‐yu
Abstract : Background: c‐MET has recently been identified as a promising novel target in non‐small cell lung cancer (NSCLC). We detected the consistency of c‐MET gene amplification in metastatic lymph nodes and tumor tissues of NSCLC patients and discuss the clinical application value of c‐MET gene amplification in metastatic lymph nodes. Methods: Real‐time fluorescent quantitative PCR was used to test tumor tissues in 368 NSCLC patients and 178 paired metastatic lymph node samples. The amplification consistency in metastatic lymph nodes and tissue samples were compared and the correlation between c‐MET gene amplification and the clinical characteristics of patients was analyzed. Results: The c‐MET gene amplification rate was 8.97% (33/368) in tumor tissues. Of the 178 paired cases, c‐MET gene amplification was positive in 7.95% (15/178) of cancerous tissues and 18.54% (33/178) of metastatic lymph nodes. c‐MET gene amplification was detected more frequently in metastatic lymph nodes than in primary cancerous tissue. When metastatic lymph nodes were used as surrogate samples of primary cancerous tissues, the sensitivity was 86.67% (13/15) and the specificity was 87.69% (143/163). Conclusions: Screening for c‐MET gene amplification in lymph node metastases could determine which patients are eligible for tyrosine kinase inhibitor therapy. Lymph node metastasis can predict c‐MET gene amplification in a primary tumor and guide the clinical use of c‐MET gene targeted drugs.